Evaluation of Some Mechanical Properties of a Maxillofacial Silicon Elastomer Reinforced with Polyester Powder - Yagthan Mohammed Haider; Zainab Salih Abdullah; Ghasak H. Jani; Norehan Mokhtar (Wiley, 2019)
Maxillofacial silicone elastomers are used to replace and reconstruct missing facial parts for patients with trauma or a certain disease. Although commonly favorable silicone elastomers are not ideal in properties, many studies have been carried out to improve their mechanical properties and to come out with ideal maxillofacial prosthetic materials, so as to render patients with the best maxillofacial prostheses. The aim of the current study is to evaluate the effect of addition of different concentrations of polyester powder on hardness, tear strength, surface roughness, and tensile strength of maxillofacial A-2186 RTV silicone elastomers. Polyester powder was added to the silicone elastomer in the concentrations of 1%, 3% and 5% by using an electronic digital balance, compared with the control group of 0% polyester filler. The shore A hardness test was done according to ASTM D 2240 standards. The tear test was done according to ASTM D624 type C standards. The tensile test was done according to ISO specification number 37:2011. The surface roughness test was performed according to ISO 7619-1 2010 specifications. The data collected were then analyzed using one-way analysis of variance (ANOVA) and post hoc and Fisher's LSD tests. All three groups showed a highly significant increase in tear strength, tensile strength, hardness, and roughness, compared to the control group. Reinforcement of A-2186 Platinum RTV Silicone Elastomer with 5% polyester significantly improved the mechanical properties tested in this study.